2021
DOI: 10.3389/fonc.2021.670396
|View full text |Cite
|
Sign up to set email alerts
|

Mucin-1 Protein Is a Prognostic Marker for Pancreatic Ductal Adenocarcinoma: Results From the CONKO-001 Study

Abstract: BackgroundThe Mucin-family protein, MUC1, impacts on carcinogenesis and tumor invasion. We evaluated the impact of MUC1 expression on outcome in a cohort of 158 patients with resected pancreatic ductal adenocarcinomas (PDAC) in the CONKO-001 study (adjuvant gemcitabine [gem] vs. observation [obs]).MethodsThe percentage of MUC1-positive tumor cells by immunohistochemistry (IHC) and the staining intensity were evaluated by two observers blinded to outcome. The numeric values of both parameters were multiplied, r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Any potency of an early biomarker relies on its expression to be consistent across different stages of cancer progression. A progressive PDAC TMA was also used to assess the status of KIF5B and SFRP2 along with MUC1, which is a routinely used PDAC progression marker [45][46][47]. These markers were consistently expressed in low grade PanINs, high grade PanINs, and in the primary adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Any potency of an early biomarker relies on its expression to be consistent across different stages of cancer progression. A progressive PDAC TMA was also used to assess the status of KIF5B and SFRP2 along with MUC1, which is a routinely used PDAC progression marker [45][46][47]. These markers were consistently expressed in low grade PanINs, high grade PanINs, and in the primary adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The results are in line with a study from Liu et al who showed a statistically significant association between a high expression of MUC1 and male gender as well as lymph node metastasis in a series of MuEp [ 40 ] as well as with data from Alos et al who likewise showed an association between a high MUC1 expression and lymph node metastasis in MuEp [ 41 ]. Also, MUC1 serves as an adaptor protein leading to cell proliferation, infiltration into the extracellular matrix, and deregulation of apoptosis [ 15 , 16 ]. These findings suggest that MUC1 expressing SGC might represent a subset of tumors with a higher likelihood of lymphovasular invasion, lymph node metastasis, extracapsular extension and consequently, a particular need for targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Mucins are a family of glycosylated proteins produced by epithelial tissues in humans. Mucin-1 (MUC1), also known as CA 15–3, is a type I transmembrane glycoprotein with a cytoplasmatic tail serving as an adaptor protein connected with kinases and further cell signaling proteins leading to cell proliferation, infiltration into the extracellular matrix, deregulation of apoptosis and changes in the adhesion state of the cell [ 15 , 16 ]. It has been shown that in cancer cells with MUC1-overexpression phosphatidylinositol 3-kinase (PI3K), mitogen-activated protein kinase (MAPK) and wingless type (Wnt) pathways are overstimulated [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The paraffin-embedded tissue sections derived from transplanted neoplasms in the sh-NC or sh-circFIG 4 groups To assess the degree of positive staining for ki-67 antibody in tumor cells, the immunoreactivity score (IRS) was evaluated by referring to previous report of Striefler et al 18 in which the final total score was generated by the multiplication product of the intensity score (the staining intensity) and the proportion score (the percentage of positive cells). The intensity score was defined as follows: negative = 0 (no staining), weak staining = 1, moderate staining = 2, strong staining = 3.…”
Section: Immunohistochemistry Assaymentioning
confidence: 99%